PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Bereshia Elshaday Natalia Aritonang; Regina Sipayung; Antonius Remigius Abi; Darinda Sofia Tanjung; Irmina Pinem (Universitas Negeri Medan, 2026)
This study aims to determine the effect of the Wordwall-assisted Problem-Based Learning model on student learning outcomes in the IPAS IV subject at SD Negeri 060841 Medan Petisah in the 2024/2025 academic year. The research method used is an experimental method with a quantitative research design, and the sample size is 30 students selected using the total sampling technique. The research instruments include a questionnaire and a multiple-choice test. The students' learning outcomes show an average pretest score of 57.2, while the average posttest score is 82.53, and the questionnaire yielded an average score of 75.2. The level of success in student learning outcomes increased, as evidenced by the correlation test results obtained, which were 0.723, meaning that r_calculated ≥ r_table 0.723 ≥ 0.361. Furthermore, the hypothesis testing (t-test) showed t_calculated ≥ t_table, i.e., 5.544 ≥ 1.697, so Ha was accepted. This indicates that there is a significant positive effect of the Problem-Based Learning Model Assisted by Wordwall on Student Learning Outcomes in the IPAS IV Subject at SD Negeri 060841 Medan Petisah in the 2024/2025 Academic Year.